PENDIDIKAN POLITIK KOALISI PEREMPUAN YOGYAKARTA WILAYAH YOGYAKARTA 2000-2008 - Sri Roviana (Jurnal Sosiologi Reflektif, 2015)
Indonesian women are marginalized in political decision making. Various of women organizations before independence considered that political education to women as an important step. The Coalition of Women’s programs focus on political education. The method used in this research is descriptive, explorative, exploratory for illustrated with clear linkages between issues. Data mining is done by in-depth interviews as the primary data and the study of literature as secondary data. The data were analyzed by the social movement theory. The reseult of this research namely : First, political education into the long-term effort to equip women to have a political vision in the lives of individuals, groups or state. Second, the Coalition of Women’s Yogyakarta region because of ideology and values held by diverse, have run into trouble when mobilization in the fild. Women’s Coalition Yogyakarta region as a mass movement, depending on the actors and major donors. Third, the Coalition of Women in the Yogyakarta area represents the activity is more elite and educated class, represented by its management, not a representation of the existing member base in the hamlets with the appearance of weak economic class and low education. Fourth, because the mass relations of women with a donor agency that is so close, without realizing the long term has made a run when there is mass movement of funds from donors, and shuffl away when the donor agency. The summary of research namely: Indonesian Women’s Coalition Yogyakarta region actually has qualifid as an embryo or a sprinkling of new social movements, but the growth of this movement must deal Weakness factors are present in the middle of the road: diffiulty building shared ideology, political representation, which represented the elite organization, no consolidation organizing base, dependence on donor funding agencies and lack of self-help and self-fiancing members to conduct political education of women.